Clipping of Basilar and Middle Cerebral Artery Aneurysms: 2‐dimensional operative video. Issue 3 (September 2020) - Hendricks, Benjamin K.; Spetzler, Robert F.
Abstract : N/A: Careful preoperative planning for patients with multiple intracranial aneurysms is paramount given the importance of an appropriate trajectory and exposure for each aneurysm that will be clipped. The general principle is to clip aneurysms in a retrograde manner, such that more distal aneurysms are clipped earlier, and more superficial aneurysms are clipped later. This patient had unruptured middle cerebral artery (MCA) and basilar artery (BA) apex aneurysms and elected for surgical clipping of both lesions. An orbitozygomatic craniotomy ipsilateral to the MCA aneurysm was performed to permit clipping of both lesions. The dissection initially focused on exposure of the MCA aneurysm and then focused on the carotid‐oculomotor triangle to permit basilar apex exposure and aneurysm clipping. The MCA aneurysm was clipped second. Postoperative imaging demonstrated complete obliteration of both aneurysms. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .